Penerapan Metode Fuzzy Inference System (Fis) Untuk Penilaian Kinerja Karyawan Level Supervisor-Manager Pada Pt. Tpil Logistics Jakarta - Wulan Dari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Qualified human resources are human resources who have high competence and skills that can promote the company. The performance appraisal of a company is very important to evaluate and plan the future. Employee performance assessment absolutely must be done in order to determine the quality of human resources that exist in the company whether it is satisfactory or unsatisfactory. Therefore, every company has a different way of doing employee performance appraisal process. Each company is always faced with the problem of employee performance appraisal. In addition to giving motivational , leadership also provide an assessment of employee performance evaluation materials. The author tries to give an idea to predict the performance of employees using Fuzzy Inference System to determine a system where a better decision